Gas Transport Arising from the Decomposition of Methane Hydrates in the Sediments of the Arctic Shelf to the Atmosphere: Numerical Modeling - Mariia Trimonova; Nikolay Baryshnikov; Sergey Turuntaev (Atmosphere)
This study investigates the transport of methane released from gas hydrate decomposition through sedimentary layers to quantify its flux into the atmosphere, a critical process given methane’s role as a major greenhouse gas. A novel methodology was developed to model two-phase, unsteady gas flow in regions of hydrate decomposition, incorporating key factors such as relative permeability curves, capillary pressure, hydrostatics, and gas diffusion. Numerical simulations revealed that to achieve a gas front rise rate of 7 m/year, the gas accumulation rate must not exceed 10−8 kg/m3·s. At higher accumulation rates (10−6 kg/m3·s), gas diffusion has minimal impact on the saturation front movement, whereas at lower rates (10−8 kg/m3·s), diffusion significantly affects the front’s behavior. The study also established that the critical gas accumulation rate required to trigger sediment blowout in the hydrate decomposition zone is approximately 10−6 kg/m3·s, several orders of magnitude greater than typical bubble gas fluxes observed at the ocean surface. The proposed model improves the ability to predict the contribution of Arctic shelf methane hydrate decomposition to atmospheric methane concentrations.